(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The term quality education (academic excellence) has become mantra of present day education system, whether it is elementary, secondary or higher education. Learning, teaching and interaction are basic components of an education process. Higher education plays a key role in society’s progress and the economy’s development. In the 21st century requirements, quality higher education must aim to develop good, thoughtful, well-rounded and creative individuals. Foundation of human skills reveals, no two persons are similar in behaviour, which leads to human diversity. Education system has ‘Learner’s Centered Approach.’ Learning is a permanent change in behaviour through education, training, practice and experience. Learning is an important exercise for acquisition of knowledge. Due to learning, it is possible to enhance the thinking process. Skill is the specific capacity to physically manipulate objects. In higher education skills have the great importance and utilization of different skills for learning is the need of time. Knowledge acquisition skills are helpful for active participation of students in learning process. Knowledge acquisition skills will assist to make higher education more creative, productive and effective. In the present paper an attempt is made to highlight significant skills required for knowledge acquisition or learning in higher education.